Oxidation electrolyte and electrolytic oxidation method of alloy surface
By adding fluoride, hydroxide and other components to the oxidized electrolyte, an alkaline oxidized electrolyte is solved, and the problems of high oxidation voltage and unstable film layer in the existing oxidized electrolyte are achieved, and efficient and stable oxide film formation is achieved, improving wear and corrosion resistance.
Patent Information
- Application Number
- CN202411793612.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
During the electrolytic oxidation process, the existing oxidation electrolytes have problems such as high oxidation voltage, thin film layer thickness, slow film layer growth rate and unstable film layer components, resulting in insufficient anti-wear and corrosion resistance of the oxide film.
An oxidized electrolyte solution including main film forming agent (fluoride), auxiliary film forming agent (hydroxide), film forming stabilizer (sodium tetraborate, etc.), low-pressure arc-starting additive (potassium sodium tartrate, etc.) and water is used to control the concentration and proportion of each component to form an alkali oxidized electrolyte with a pH value of 11.5 to 13.5.
The oxidation voltage of electrolytic oxidation technology is reduced, the film formation efficiency and chemical stability of the film layer are improved, the anti-wear and corrosion resistance of the oxide film is enhanced, the service life of the electrolyte is extended, and the purpose of green and low-carbon with low energy consumption and high efficiency is achieved.
Smart Images

Figure CN119615325A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoelectrode materials, and in particular to an oxidation electrolyte and an electrolytic oxidation method for an alloy surface. Background Art
[0002] Aluminum alloy and magnesium alloy are the most widely used metal materials in the process of equipment lightweighting due to their low relative density, light weight, high strength, good thermal and electrical conductivity and excellent processing performance. However, due to the relatively low surface hardness and high electrochemical activity of the two metals, wear and corrosion are inevitable during the use of the materials. The wear and corrosion failure caused by this seriously limits the application of the two lightweight metal materials in various fields. Therefore, proper surface oxidation treatment of the material is the most economical and effective method to improve its wear resistance and corrosion resistance. At present, the commonly used surface oxidation treatment methods are chemical oxidation, anodic oxidation and micro-arc oxidation. Among them, the chemical oxidation method has simple equipment and convenient operation, but the oxide film is thin, and the wear resistance and corrosion resistance are relatively poor. It can usually only be used for decoration and temporary protection. The oxide film obtained by the anodic oxidation method using low voltage (0-100V) and high current is relatively high in hardness, and the wear resistance and corrosion resistance are significantly improved, but the solution used is generally acidic, and the environmental pollution during the treatment process is serious. The oxide film prepared by micro-arc oxidation has high hardness, good wear resistance and corrosion resistance, the electrolyte is alkaline, and the environmental pollution is also small, but the voltage used is high (400-700V), the oxidation treatment time is long, the energy consumption is large, and the cost is high.
[0003] With the continuous advancement of energy conservation, emission reduction, and green and low-carbon development concepts, improving the stability and service life of oxidation electrolytes, reducing energy consumption during electrolytic oxidation, and improving oxidation film-forming efficiency have become the focus of researchers. However, although the arc starting voltage and oxidation time can be reduced by optimizing the design of oxidation electrolyte components in the prior art, the termination voltage of the electrolytic oxidation process is still high, the thickness of the oxide film is thin, the film growth rate is slow, and the film components are mainly oxides of matrix elements such as magnesium or aluminum. However, oxides such as aluminum oxide and magnesium oxide have poor chemical stability in weakly acidic or neutral aqueous solutions, resulting in insufficient wear resistance and corrosion resistance of the coating. Summary of the invention
[0004] In view of this, the object of the present invention is to provide an oxidizing electrolyte and an electrolytic oxidation method for an alloy surface. The oxidizing electrolyte of the present invention can reduce the oxidation voltage of the electrolytic oxidation technology, and has the advantages of high film forming efficiency and good chemical stability of film layer components.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an oxidizing electrolyte, comprising a main film-forming agent, an auxiliary film-forming agent, a film-forming stabilizer, a low-voltage arc-starting aid and water;
[0007] The main film-forming agent is fluoride; the concentration of the main film-forming agent in the oxidizing electrolyte is 70-150 g / L;
[0008] The oxidizing electrolyte is alkaline;
[0009] The pH of the oxidation electrolyte is 11.5-13.5.
[0010] Preferably, the main film-forming agent includes one or more of potassium fluoride, ammonium fluoride and sodium fluoride.
[0011] Preferably, the mass ratio of potassium fluoride, ammonium fluoride and sodium fluoride in the main film-forming agent is (0-100): (0-80): (0-60);
[0012] And the dosage of potassium fluoride, ammonium fluoride and sodium fluoride is not 0 at the same time.
[0013] Preferably, the concentration of the auxiliary film-forming agent in the oxidation electrolyte is 40 to 90 g / L;
[0014] The auxiliary film-forming agent includes one or more of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide.
[0015] Preferably, the mass ratio of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide in the auxiliary film-forming agent is (0-50): (0-40): (0-30): (0-20);
[0016] The amounts of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide are not all 0 at the same time.
[0017] Preferably, the concentration of the film-forming stabilizer in the oxidizing electrolyte is 20 to 50 g / L.
[0018] Preferably, the film-forming stabilizer includes one or more of sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate.
[0019] Preferably, the mass ratio of sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate in the film-forming stabilizer is (0-30): (0-25): (0-20): (0-15);
[0020] The dosage of the sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate is not 0 at the same time.
[0021] Preferably, the concentration of the low-voltage arc-starting aid in the oxidizing electrolyte is 10 to 30 g / L;
[0022] The low-voltage arc-starting auxiliary agent includes one or more of potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate;
[0023] The mass ratio of potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate in the low-voltage arc-starting aid is (0-20): (0-15): (0-15): (0-10);
[0024] And the dosage of the potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate is not 0 at the same time.
[0025] The present invention also provides an alloy surface electrolytic oxidation method, comprising the following steps:
[0026] The alloy substrate is used as an anode and the stainless steel coil is used as a cathode, and the anode is placed in an oxidizing electrolyte for electrolytic oxidation treatment to obtain an oxide film layer;
[0027] The alloy matrix is an aluminum alloy or a magnesium alloy;
[0028] The positive voltage of the electrolytic oxidation treatment is 50 to 150 V, and the negative voltage is 0 to 30 V;
[0029] The oxidizing electrolyte is the oxidizing electrolyte described in the above technical solution.
[0030] The present invention provides an oxidizing electrolyte, comprising a main film-forming agent, an auxiliary film-forming agent, a film-forming stabilizer, a low-voltage arc-starting aid and water; the main film-forming agent is a fluoride; the concentration of the main film-forming agent in the oxidizing electrolyte is 70 to 150 g / L; the oxidizing electrolyte is alkaline; the pH of the oxidizing electrolyte is 11.5 to 13.5. The anions in the oxidizing electrolyte of the present invention are mainly F - Ions and OH - Ion composition, F -Ions have the characteristic of enhancing the interface layer, and are easy to form a dense and well-passivated interface barrier layer on the metal surface, which is conducive to reducing the electrolysis voltage. The fluorinated film layer components prepared by participating in the film-forming process have the characteristics of good chemical stability. In addition, high concentrations of anions can greatly improve the ionic conductivity of the oxidation electrolyte, which can make the film-forming efficiency of the oxidation process high. At the same time, high ion concentrations are easy to form ionic complexes, which is conducive to improving the stability and service life of the electrolyte. Due to the strong complexation of a large number of coordination compounds in the solution on metal ions, the service life of the solution can be further improved. At the same time, the oxidation electrolyte can be recycled and reused by adding the main film-forming agent or concentrated electrolyte, thereby truly achieving the purpose of low energy consumption, high efficiency, green and low carbon. The oxidation electrolyte of the present invention is used in the electrolytic oxidation technology, which has a wide range of applications and is suitable for the treatment of the surfaces of various grades of aluminum alloys and magnesium alloys. It is also suitable for the surfaces of parts with complex structures formed by processing under this material.
[0031] The present invention also provides an electrolytic oxidation method for an alloy surface, comprising the following steps: using an alloy substrate as an anode and a stainless steel coil as a cathode, placing the anode in an oxidizing electrolyte for electrolytic oxidation treatment to obtain an oxide film; the alloy substrate is an aluminum alloy or a magnesium alloy; and the oxidizing electrolyte is the oxidizing electrolyte described in the above technical solution. According to the description of the embodiment, the growth rate of the oxide film prepared on the surface of an aluminum alloy using the electrolytic oxidation method of the present invention is 5 to 10 μm / min, and the film layer is a composite formed by aluminum oxide and aluminum fluoride. The growth rate of the oxide film prepared on the surface of a magnesium alloy is 10 to 15 μm / min, and the film layer is a composite composed of magnesium oxide and magnesium fluoride. The wear rate of the oxide film on the surface of an aluminum alloy is 2.5×10 -5 ~7.5×10 -5 mm / N·m, and the wear rate of the oxide film on the surface of the magnesium alloy is 1.2×10 -3 ~4×10 -3 mm / N·m. The salt spray corrosion resistance of the oxide film on the surface of aluminum alloy is 500-1000h, and the salt spray corrosion resistance of the oxide film on the surface of magnesium alloy is 100-500h. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The microstructure and composition diagram of the oxide film described in Example 1;
[0033] Figure 2 The microstructure and composition diagram of the oxide film described in Example 2;
[0034] Figure 3 This is a macroscopic comparison diagram of the oxide film salt spray corrosion for 0 to 1000 hours described in Example 1;
[0035] Figure 4This is a macroscopic comparison diagram of the salt spray corrosion of the oxide film described in Example 2 for 0 to 500 hours. DETAILED DESCRIPTION
[0036] The present invention provides an oxidizing electrolyte, comprising a main film-forming agent, an auxiliary film-forming agent, a film-forming stabilizer, a low-voltage arc-starting aid and water;
[0037] The main film-forming agent is fluoride; the concentration of the main film-forming agent in the oxidizing electrolyte is 70-150 g / L;
[0038] The oxidizing electrolyte is alkaline;
[0039] The pH of the oxidation electrolyte is 11.5-13.5.
[0040] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0041] In the present invention, the pH of the oxidation electrolyte is 11.5 to 13.5, preferably 12 to 13. In an embodiment of the present invention, the pH of the oxidation electrolyte may be 12.5, 13.5, 12, 11.5 or 13.
[0042] In the present invention, the concentration of the main film-forming agent in the oxidizing electrolyte is 70-150 g / L, preferably 80-140 g / L, and more preferably 90-120 g / L; the main film-forming agent preferably includes one or more of potassium fluoride, ammonium fluoride and sodium fluoride, and more preferably includes potassium fluoride, ammonium fluoride and sodium fluoride in a mass ratio of (0-100): (0-80): (0-60), and the amount of potassium fluoride, ammonium fluoride and sodium fluoride is not 0 at the same time. In an embodiment of the present invention, the main film-forming agent can be potassium fluoride, ammonium fluoride and sodium fluoride in a mass ratio of 30:50:40, potassium fluoride and sodium fluoride in a mass ratio of 10:60, potassium fluoride and ammonium fluoride in a mass ratio of 80:30, ammonium fluoride and sodium fluoride in a mass ratio of 80:10, potassium fluoride or ammonium fluoride and sodium fluoride in a mass ratio of 40:10.
[0043] In the present invention, the role of controlling the type and amount of the main film-forming agent within the above range is to provide anion electrolyte to intervene in the electrolytic oxidation process and affect the structure and composition of the oxide film.
[0044] In the present invention, the concentration of the auxiliary film-forming agent in the oxidizing electrolyte is preferably 40-90 g / L, more preferably 50-80 g / L, and most preferably 60-70 g / L; the auxiliary film-forming agent preferably includes one or more of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide, and more preferably includes sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of (0-50):(0-40):(0-30):(0-20), and the amounts of the sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide are not 0 at the same time. In an embodiment of the present invention, the auxiliary film-forming agent can be sodium hydroxide, potassium hydroxide and lithium hydroxide in a mass ratio of 10:20:20, sodium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 50:10:5, potassium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 40:30:10, sodium hydroxide, potassium hydroxide and barium hydroxide in a mass ratio of 40:20:30, or sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 10:10:10:10.
[0045] In the present invention, the role of controlling the type and amount of the auxiliary film-forming agent within the above range is to affect the growth rate of the oxide film.
[0046] In the present invention, the concentration of the film-forming stabilizer in the oxidation electrolyte is preferably 20-50 g / L, more preferably 30-40 g / L, and most preferably 33-36 g / L; the film-forming stabilizer includes one or more of sodium tetraborate, sodium pyrophosphate, sodium oxalate, and sodium carbonate. More preferably, the mass ratio of sodium tetraborate, sodium pyrophosphate, sodium oxalate, and sodium carbonate is (0-30): (0-25): (0-20): (0-15); and the amount of sodium tetraborate, sodium pyrophosphate, sodium oxalate, and sodium carbonate is not 0 at the same time. In an embodiment of the present invention, the film-forming stabilizer can be sodium tetraborate, sodium pyrophosphate and sodium oxalate in a mass ratio of 10:5:20, sodium pyrophosphate, sodium oxalate and sodium carbonate in a mass ratio of 25:5:15, sodium tetraborate, sodium oxalate and sodium carbonate in a mass ratio of 30:10:10, sodium tetraborate, sodium pyrophosphate and sodium carbonate in a mass ratio of 10:10:5, or sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate in a mass ratio of 5:5:5:5.
[0047] In the present invention, the type and amount of the film-forming stabilizer are controlled within the above range to affect the stability and consistency of the oxide film growth process.
[0048] In the present invention, the concentration of the low-voltage arc-starting aid in the oxidizing electrolyte is preferably 10-30 g / L, more preferably 15-25 g / L, and most preferably 18-22 g / L; the mass ratio of potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate in the low-voltage arc-starting aid is preferably (0-20): (0-15): (0-15): (0-10), and the amount of potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate is not 0 at the same time. In an embodiment of the present invention, the low-voltage arc-starting aid can be potassium sodium tartrate, disodium oxalate tetraacetate and sodium gluconate in a mass ratio of 5:5:5, potassium sodium tartrate, disodium oxalate tetraacetate and sodium citrate in a mass ratio of 5:5:15, disodium oxalate tetraacetate and sodium gluconate in a mass ratio of 15:5, potassium sodium tartrate and sodium citrate in a mass ratio of 5:5, or potassium sodium tartrate and sodium gluconate in a mass ratio of 20:10.
[0049] In the present invention, the role of controlling the type and amount of the low-voltage arc-starting aid within the above range is to improve the density of the metal surface barrier layer, reduce the arc-starting voltage and reaction termination voltage during the oxidation process, and significantly reduce the energy consumption during the oxidation process.
[0050] In the present invention, the water is preferably deionized water.
[0051] In the present invention, the preparation process of the oxidation electrolyte is preferably: a main film-forming agent, an auxiliary film-forming agent, a film-forming stabilizer, a low-voltage arc-starting aid and water are mixed to obtain the oxidation electrolyte.
[0052] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention does not have any special limitation on the stirring process, and the stirring process may be carried out using a process well known to those skilled in the art.
[0053] The present invention also provides an alloy surface electrolytic oxidation method, comprising the following steps:
[0054] The alloy substrate is used as an anode and the stainless steel coil is used as a cathode, and the anode is placed in an oxidizing electrolyte for electrolytic oxidation treatment to obtain an oxide film layer;
[0055] The alloy matrix is an aluminum alloy or a magnesium alloy;
[0056] The oxidizing electrolyte is the oxidizing electrolyte described in the above technical solution.
[0057] The present invention does not have any special limitation on the specific grades of the aluminum alloy or magnesium alloy, and any grades known to those skilled in the art can be used. In an embodiment of the present invention, the alloy matrix is an aluminum alloy of model 6061 or a magnesium alloy of model AZ91D; the aluminum alloy of model 6061 includes, in terms of mass percentage, 0.4-0.8wt% Si, 0.15-0.4wt% Cu, 0.7wt% Fe, 0.8-1.2wt% Mg, 0.15wt% Mn, 0.25wt% Zn, 0.04-0.35wt% Cr, 0.15wt% Ti and the balance Al; the magnesium alloy of model AZ91D includes, in terms of mass percentage, 8.5-9.5wt% Al, 0.45-0.9wt% Zn, 0.17-0.4wt% Mn, 0-0.05wt% Si, 0-0.025wt% Cu, 0-0.004wt% Fe, 0-0.001wt% Ni and the balance Mg.
[0058] Before carrying out the electrolytic oxidation treatment, the present invention preferably pre-treats the alloy substrate, and the pre-treatment preferably includes polishing, cleaning and drying performed in sequence; the polishing is preferably performed using water-resistant sandpaper; the present invention does not have any special restrictions on the cleaning and drying process, and the process familiar to those skilled in the art can be used.
[0059] In the present invention, the electrolytic oxidation treatment is preferably carried out under conditions of circulating cooling and stirring; the circulating cooling conditions are preferably provided by a cooling water circulation system; the present invention does not have any special limitation on the stirring process, and the process familiar to those skilled in the art can be used.
[0060] In the present invention, the electrolytic oxidation treatment preferably adopts the voltage mode of a pulse power supply; the frequency of the electrolytic oxidation treatment is preferably 100-2000Hz, more preferably 400-1500Hz, and most preferably 800-1200Hz; the duty cycle is preferably 8%-30%, more preferably 12%-25%, and most preferably 18%-21%; the positive voltage is preferably 50-150V, more preferably 70-130V, and most preferably 90-110V; the negative voltage is preferably 0-30V, more preferably 5-25V, and most preferably 10-20V; the treatment time is preferably 2-8min, more preferably 3-7min, and most preferably 4-6min.
[0061] In the present invention, the reactions and changes occurring during the electrolytic oxidation treatment process are the process in which anions such as fluoride ions and hydroxide ions in the electrolyte undergo rapid oxidation or fluorination reactions with alloy elements of the substrate under the drive of an electric field to form a film layer.
[0062] After the electrolytic oxidation treatment is completed, the present invention also preferably includes cleaning and drying performed in sequence; the cleaning is preferably performed using deionized water; the present invention does not have any special limitations on the cleaning and drying process, and the cleaning and drying process may be performed using a process familiar to those skilled in the art.
[0063] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] Example 1
[0065] Add a main film-forming agent (potassium fluoride and ammonium fluoride in a mass ratio of 80:30), an auxiliary film-forming agent (sodium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 50:10:5), a film-forming stabilizer (sodium tetraborate, sodium pyrophosphate and sodium oxalate in a mass ratio of 10:5:20) and a low-voltage arc-starting aid (disodium oxalate tetraacetate and sodium gluconate in a mass ratio of 15:5) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 110 g / L, the auxiliary film-forming agent is 65 g / L, the film-forming stabilizer is 35 g / L, and the low-voltage arc-starting aid is 20 g / L), and the pH value is 12.5;
[0066] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0067] The pretreated aluminum alloy substrate is used as an anode and a stainless steel coil is used as a cathode. The anode is placed in the oxidation electrolyte, a cooling water circulation system is turned on, and a pulse power supply voltage mode is adopted. Under the conditions of a power supply frequency of 800 Hz, a duty cycle of 15%, a positive voltage of 90 V, and a negative voltage of 12 V, the pretreated aluminum alloy substrate is subjected to electrolytic oxidation treatment for 5 minutes while stirring. After the electrolytic oxidation treatment is completed, the substrate is rinsed with tap water and deionized water in turn and blown dry to obtain an oxide film ( Figure 1 is the microstructure and composition diagram of the oxide film, Figure 1 It can be seen that the oxide film is composed of a composite of aluminum oxide and aluminum fluoride);
[0068] The thickness of the oxide film is measured according to GB / T 4957-2003 "Eddy current method for measuring the thickness of non-conductive coatings on non-magnetic base metals", and the thickness of the oxide film is 40 μm;
[0069] According to the test standard GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", the oxide film is subjected to a salt spray environment accelerated corrosion test. Figure 3 is a macroscopic comparison diagram of the oxide film salt spray corrosion from 0 to 1000h, Figure 3 It can be seen that the salt spray corrosion resistance of the oxide film is 1000h;
[0070] The wear resistance of different oxide films was evaluated by a reciprocating friction and wear tester. A Si3N4 ceramic ball with a diameter of φ6 was used as the friction pair. The parameters of the friction process were set to a frequency of 5 Hz, a stroke of 5 mm, a load of 2 N, a friction test time of 30 min, an experimental environment temperature of room temperature, and a relative humidity of about 40%. After the friction and wear performance test, the wear scar volume was measured using a non-contact optical profilometer to calculate the wear rate. The wear rate of the oxide film was 2.5×10 -5 mm / N·m.
[0071] Example 2
[0072] Referring to Example 1, the difference is that the aluminum alloy with the grade of 6061 is replaced by the magnesium alloy of AZ91D to obtain the oxide film ( Figure 2 is a microstructure diagram and composition diagram of the oxide film, wherein the oxide film is a composite of magnesium oxide and magnesium fluoride; Figure 1 and Figure 2 It can be seen from the comparison that the appearance color of the film layer prepared under the same preparation conditions is basically gray, with good uniformity. Affected by the composition of the alloy matrix, the composition and microstructure of the oxide film layer are somewhat different, which affects the wear resistance and salt spray corrosion resistance of the oxide film);
[0073] The thickness, salt spray corrosion resistance and wear rate of the oxide film were tested according to the test method described in Example 1;
[0074] The thickness of the oxide film is 70 μm;
[0075] Figure 4 is a macroscopic comparison diagram of the oxide film salt spray corrosion from 0 to 500h, Figure 4 It can be seen that the salt spray corrosion resistance of the oxide film is 500h;
[0076] The wear rate of the oxide film is 1.2×10 -3 mm / N·m.
[0077] Example 3
[0078] Add a main film-forming agent (potassium fluoride and sodium fluoride in a mass ratio of 10:60), an auxiliary film-forming agent (sodium pyrophosphate, sodium oxalate and sodium carbonate in a mass ratio of 40:20:30), a film-forming stabilizer (sodium tetraborate, sodium pyrophosphate and sodium oxalate in a mass ratio of 10:5:20) and a low-voltage arc-starting aid (potassium sodium tartrate, disodium oxalate and sodium citrate in a mass ratio of 5:5:15) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 70 g / L, the auxiliary film-forming agent is 90 g / L, the film-forming stabilizer is 45 g / L, and the low-voltage arc-starting aid is 25 g / L), and the pH value is 13.5;
[0079] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0080] The pretreated aluminum alloy substrate was used as an anode and a stainless steel coil was used as a cathode. The anode was placed in the oxidation electrolyte. The cooling water circulation system was turned on. The voltage mode of the pulse power supply was adopted. Under the conditions of a power supply frequency of 2000 Hz, a duty cycle of 30%, a positive voltage of 150 V, and a negative voltage of 0 V, the pretreated aluminum alloy substrate was subjected to electrolytic oxidation treatment for 8 minutes under stirring. After the electrolytic oxidation treatment was completed, the substrate was rinsed with tap water and deionized water in turn and dried to obtain an oxide film (thickness of 50 μm, the film layer was a composite of aluminum oxide and aluminum fluoride, and the wear rate was 3.5×10 -5 mm / N·m, and salt spray corrosion resistance is 900h).
[0081] Example 4
[0082] Referring to Example 3, the difference is that the aluminum alloy with the grade of 6061 is replaced by the magnesium alloy of AZ91D, and the oxide film (thickness of 80 μm, the film layer is a composite of magnesium oxide and magnesium fluoride, and the wear rate is 2.5×10 -3 mm / N·m, and salt spray corrosion resistance is 450h).
[0083] Example 5
[0084] Add a main film-forming agent (potassium fluoride, ammonium fluoride and sodium fluoride in a mass ratio of 30:50:40), an auxiliary film-forming agent (sodium hydroxide, potassium hydroxide and lithium hydroxide in a mass ratio of 10:20:20), a film-forming stabilizer (sodium tetraborate, sodium pyrophosphate and sodium carbonate in a mass ratio of 10:10:5) and a low-voltage arc-starting aid (potassium sodium tartrate, disodium oxalate tetraacetate and sodium gluconate in a mass ratio of 5:5:5) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 120 g / L, the auxiliary film-forming agent is 50 g / L, the film-forming stabilizer is 25 g / L, and the low-voltage arc-starting aid is 15 g / L), and the pH value is 12;
[0085] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0086] The pretreated aluminum alloy substrate was used as an anode and a stainless steel coil was used as a cathode. The anode was placed in the oxidation electrolyte. The cooling water circulation system was turned on. The voltage mode of the pulse power supply was adopted. Under the conditions of a power supply frequency of 500 Hz, a duty cycle of 20%, a positive voltage of 70 V, and a negative voltage of 20 V, the pretreated aluminum alloy substrate was subjected to electrolytic oxidation treatment for 3 min under stirring. After the electrolytic oxidation treatment was completed, the substrate was rinsed with tap water and deionized water in turn and dried to obtain an oxide film (thickness of 30 μm, the film layer was a composite of aluminum oxide and aluminum fluoride, and the wear rate was 5.0×10 -5 mm / N·m, and salt spray corrosion resistance is 700h).
[0087] Example 6
[0088] Referring to Example 5, the difference is that the aluminum alloy with the grade of 6061 is replaced by the magnesium alloy of AZ91D, and the oxide film (thickness of 45 μm, the film layer is a composite of magnesium oxide and magnesium fluoride, and the wear rate is 3.2×10 -3 mm / N·m, salt spray corrosion resistance is 250h).
[0089] Example 7
[0090] Add a main film-forming agent (potassium fluoride, ammonium fluoride and sodium fluoride in a mass ratio of 100:40:10), an auxiliary film-forming agent (sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 10:10:10:10), a film-forming stabilizer (sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate in a mass ratio of 5:5:5:5) and a low-voltage arc-starting aid (potassium sodium tartrate and sodium citrate in a mass ratio of 5:5) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 150 g / L, the auxiliary film-forming agent is 40 g / L, the film-forming stabilizer is 20 g / L, and the low-voltage arc-starting aid is 10 g / L), and the pH value is 11.5;
[0091] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0092] The pretreated aluminum alloy substrate was used as an anode and a stainless steel coil was used as a cathode. The anode was placed in the oxidation electrolyte. The cooling water circulation system was turned on. The voltage mode of the pulse power supply was adopted. Under the conditions of a power supply frequency of 100 Hz, a duty cycle of 8%, a positive voltage of 50 V, and a negative voltage of 30 V, the pretreated aluminum alloy substrate was subjected to electrolytic oxidation treatment for 2 minutes under stirring. After the electrolytic oxidation treatment was completed, the substrate was rinsed with tap water and deionized water in turn and dried to obtain an oxide film (thickness of 15 μm, the film layer was a composite of aluminum oxide and aluminum fluoride, and the wear rate was 7.5×10 -5 mm / N·m, salt spray corrosion resistance is 500h).
[0093] Example 8
[0094] Referring to Example 7, the difference is that the aluminum alloy with the grade of 6061 is replaced by the magnesium alloy of AZ91D, and the oxide film (thickness is 25 μm, the film layer is a composite of magnesium oxide and magnesium fluoride, and the wear rate is 4.0×10 -3 mm / N·m, salt spray corrosion resistance is 100h).
[0095] Example 9
[0096] Add a main film-forming agent (ammonium fluoride and sodium fluoride in a mass ratio of 80:10), an auxiliary film-forming agent (potassium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 40:30:10), a film-forming stabilizer (sodium tetraborate, sodium oxalate and sodium carbonate in a mass ratio of 30:10:10) and a low-voltage arc-starting aid (potassium sodium tartrate and sodium gluconate in a mass ratio of 20:10) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 90 g / L, the auxiliary film-forming agent is 90 g / L, the film-forming stabilizer is 50 g / L, and the low-voltage arc-starting aid is 30 g / L), and the pH value is 13;
[0097] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0098] The pretreated aluminum alloy substrate was used as an anode and a stainless steel coil was used as a cathode. The anode was placed in the oxidation electrolyte. The cooling water circulation system was turned on. The voltage mode of the pulse power supply was adopted. Under the conditions of a power supply frequency of 1200 Hz, a duty cycle of 25%, a positive voltage of 120 V, and a negative voltage of 5 V, the pretreated aluminum alloy substrate was subjected to electrolytic oxidation treatment for 6 minutes under stirring. After the electrolytic oxidation treatment was completed, the substrate was rinsed with tap water and deionized water in turn and dried to obtain an oxide film (thickness of 25 μm, the film layer was a composite of aluminum oxide and aluminum fluoride, and the wear rate was 6.2×10 -5 mm / N·m, and salt spray corrosion resistance is 600h).
[0099] Example 10
[0100] Referring to Example 9, the difference is that the aluminum alloy with the grade of 6061 is replaced by the magnesium alloy of AZ91D, and the oxide film (thickness of 60 μm, the film layer is a composite of magnesium oxide and magnesium fluoride, and the wear rate is 1.8×10 -3 mm / N·m, salt spray corrosion resistance is 400h).
[0101] Comparative Example 1
[0102] Add a main film-forming agent (potassium fluoride, ammonium fluoride and sodium fluoride in a mass ratio of 10:10:10), an auxiliary film-forming agent (sodium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 50:10:5), a film-forming stabilizer (sodium tetraborate, sodium pyrophosphate and sodium oxalate in a mass ratio of 10:5:20) and a low-voltage arc-starting aid (disodium oxalate tetraacetate and sodium gluconate in a mass ratio of 15:5) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 30 g / L, the auxiliary film-forming agent is 65 g / L, the film-forming stabilizer is 35 g / L, and the low-voltage arc-starting aid is 20 g / L), and the pH value is 14;
[0103] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0104] The pretreated aluminum alloy substrate was used as an anode and the stainless steel coil was used as a cathode. The anode was placed in the oxidation electrolyte, the cooling water circulation system was turned on, and the voltage mode of the pulse power supply was adopted. Under the conditions of power supply frequency of 1200 Hz, duty cycle of 25%, positive voltage of 180 V, and negative voltage of 5 V, the pretreated aluminum alloy substrate was subjected to electrolytic oxidation treatment for 6 minutes under stirring. After the electrolytic oxidation treatment was completed, it was rinsed with tap water and deionized water in turn and dried to obtain an oxide film (thickness of 7 μm, the film layer was mainly aluminum oxide, and the wear rate was 1.5×10 -3 mm / N·m, and salt spray corrosion resistance is 150h).
[0105] Comparative Example 2
[0106] Referring to Comparative Example 1, the difference is that the aluminum alloy with the grade of 6061 is replaced by the magnesium alloy of AZ91D to obtain an oxide film (thickness of 10 μm, the film layer is mainly composed of magnesium oxide, and the wear rate is 6.5×10 -2 mm / N·m, and salt spray corrosion resistance is 72h).
[0107] Comparative Example 3
[0108] Add a main film-forming agent (potassium fluoride and ammonium fluoride in a mass ratio of 80:30), an auxiliary film-forming agent (sodium hydroxide, barium hydroxide and lithium hydroxide in a mass ratio of 5:5:5), a film-forming stabilizer (sodium tetraborate, sodium pyrophosphate and sodium oxalate in a mass ratio of 10:5:20) and a low-voltage arc-starting aid (disodium oxalate tetraacetate and sodium gluconate in a mass ratio of 15:5) to deionized water, and stir until dissolved to obtain an oxidizing electrolyte (the concentration of the main film-forming agent in the oxidizing electrolyte is 110 g / L, the auxiliary film-forming agent is 15 g / L, the film-forming stabilizer is 35 g / L, and the low-voltage arc-starting aid is 20 g / L), and the pH value is 10.5;
[0109] After polishing the aluminum alloy of grade 6061 with water-resistant sandpaper, the aluminum alloy was washed with tap water and deionized water in turn, and then dried to obtain a pretreated aluminum alloy substrate;
[0110] The pretreated aluminum alloy substrate was used as an anode and a stainless steel coil was used as a cathode. The anode was placed in the oxidation electrolyte. The cooling water circulation system was turned on. The voltage mode of the pulse power supply was adopted. Under the conditions of a power supply frequency of 1200 Hz, a duty cycle of 25%, a positive voltage of 120 V, and a negative voltage of 5 V, the pretreated aluminum alloy substrate was subjected to electrolytic oxidation treatment for 6 minutes under stirring. After the electrolytic oxidation treatment was completed, the substrate was rinsed with tap water and deionized water in turn and dried to obtain an oxide film (thickness of 3 μm, the film layer was composed of a composite of aluminum oxide and aluminum fluoride, and the wear rate was 4.6×10 -2 mm / N·m, and salt spray corrosion resistance is 96h).
[0111] Comparative Example 4
[0112] Refer to Comparative Example 3, the difference is that the aluminum alloy with grade 6061 is replaced by AZ91D magnesium alloy to obtain an oxide film (the thickness is 5 μm, the film layer is composed of a composite of magnesium oxide and magnesium fluoride, the wear rate is 0.72 mm / N·m, and the salt spray corrosion resistance is 36 h).
[0113] In summary, there is a synergistic effect between the type and concentration of anions in the oxidizing electrolyte of the present invention, which means that reducing the anion concentration in the oxidizing electrolyte will lead to a slower growth rate of the oxide film and a decrease in the wear and corrosion resistance of the film.
[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. An oxidizing electrolyte, characterized in that: Including main film-forming agent, auxiliary film-forming agent, film-forming stabilizer, low-pressure arc-starting aid and water; The main film-forming agent is fluoride; the concentration of the main film-forming agent in the oxidation electrolyte is 70-150 g / L; the oxidation electrolyte is alkaline; The pH of the oxidation electrolyte is 11.5-13.
5.
2. The oxidizing electrolyte according to claim 1, characterized in that The main film-forming agent includes one or more of potassium fluoride, ammonium fluoride and sodium fluoride.
3. The oxidizing electrolyte according to claim 2, characterized in that The mass ratio of potassium fluoride, ammonium fluoride and sodium fluoride in the main film-forming agent is (0-100): (0-80): (0-60); And the dosage of potassium fluoride, ammonium fluoride and sodium fluoride is not 0 at the same time.
4. The oxidizing electrolyte according to claim 1, characterized in that The concentration of the auxiliary film-forming agent in the oxidation electrolyte is 40 to 90 g / L; The auxiliary film-forming agent includes one or more of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide.
5. The oxidizing electrolyte according to claim 4, characterized in that The mass ratio of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide in the auxiliary film-forming agent is (0-50): (0-40): (0-30): (0-20); The amounts of sodium hydroxide, potassium hydroxide, barium hydroxide and lithium hydroxide are not all 0 at the same time.
6. The oxidizing electrolyte according to claim 1, characterized in that The concentration of the film-forming stabilizer in the oxidation electrolyte is 20 to 50 g / L.
7. The oxidizing electrolyte according to claim 1 or 6, characterized in that The film-forming stabilizer includes one or more of sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate.
8. The oxidizing electrolyte according to claim 7, characterized in that The mass ratio of sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate in the film-forming stabilizer is (0-30): (0-25): (0-20): (0-15); The dosage of the sodium tetraborate, sodium pyrophosphate, sodium oxalate and sodium carbonate is not 0 at the same time.
9. The oxidizing electrolyte according to claim 1, characterized in that The concentration of the low-voltage arc-starting aid in the oxidation electrolyte is 10 to 30 g / L; The low-voltage arc-starting auxiliary agent includes one or more of potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate; The mass ratio of potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate in the low-voltage arc-starting aid is (0-20): (0-15): (0-15): (0-10); And the dosage of the potassium sodium tartrate, disodium oxalate tetraacetate, sodium citrate and sodium gluconate is not 0 at the same time.
10. A method for electrolytic oxidation of an alloy surface, characterized in that: The following steps are involved: The alloy substrate is used as an anode and the stainless steel coil is used as a cathode, and the anode is placed in an oxidizing electrolyte for electrolytic oxidation treatment to obtain an oxide film layer; The alloy matrix is an aluminum alloy or a magnesium alloy; The positive voltage of the electrolytic oxidation treatment is 50 to 150 V, and the negative voltage is 0 to 30 V; The oxidizing electrolyte is the oxidizing electrolyte according to any one of claims 1 to 8.